La Lutte des classes face à l'internationalisme sportif. - Lorenzo Jalabert D'Amado (Conserveries Mémorielles)
The first World Cup in history took place in July 1930 in Uruguay. The country, which had won a few years back the football gold at Colombes (1924) and Amsterdam (1928) Olympic Games, already enjoyed a solid reputation in this sport. These international successes had triggered a massive passion in the country for the game. The holding of the World Cup in Montevideo, supported by the government, met a strong enthusiasm among the population with the exception of certain political sectors. Among those, Uruguay's Communist Party chose to totally reject the government's project while at the same time promoting an alternative model for sports, directly inspired by the Soviet Union's example. With the analysis of this communist stance we seek to participate in the efforts to historicize the first edition of the now FIFA's flagship tournament. This important sporting event, scarcely studied by current historiography, is yet fundamental given its leading role in the establishment, during the interwar period, of world's biggests sports competitions.